Chaguaramas development plan (1988) review - Planviron Limited. (Planviron Limited., 2011)
A review of the 1988 development plan for Chaguarams, updating data and revising proposals. Presenting information on national parks, land use and socio-economic issues, marine and terrestial ecology, ecotourism, planning concerns and design guidelines.
Keywords: Urban planning – Chaguaramas, History – Chaguaramas, Environment – Chaguaramas, National parks – Chaguaramas, Environment management – Chaguaramas, Infrastructure – Chaguaramas, Demographics – Chaguaramas, Pollution – Chaguaramas, Ecotourism Chaguaramas